Enrichment Book of Writing Persuasive Texts Oriented Creative Thinking Skills Containing Human Values - Fatahillah, Muhammad Tubagus; Subyantoro, Subyantoro; Haryadi, Haryadi (Universitas Negeri Semarang, 2022)
The existence of books in circulation related to the skills of writing persuasive texts in general still presents material on the knowledge aspect. Although there is material on the skill aspect, but its existence is not optimal to achieve learning objectives. Not only the material, but also the existence of the book must be adapted to the demands of the times and must have an impact on the personality so that students in addition to excelling in academics are also strong in character. Therefore, books are needed to deepen the material for writing persuasive texts. The purpose of the research was to compile a prototype of an enrichment book to write persuasive texts oriented to creative thinking skills with human values. The research design used Research and Development (R&D) which was carried out in three stages, namely (1) potential and problems, (2) data collection, (3) product prototype design. The results of this study was an enrichment book prototype for writing persuasive texts oriented to creative thinking skills containing human values which were arranged by paying attention to (1) material aspects that uses the principles of meaningfulness, authenticity, assessment, and functionality, (2) presentation aspects using the principle of cohesiveness, (3 ) the linguistic aspect used the communicative principle, (4) the graphic aspect used the cohesive principle, (5) the creative thinking aspect used the linked principle, and (6) the human value aspect used the linked principle. Based on these aspects, the book section consisted of (1) the book cover, (2) the beginning of the book, (3) the contents of the book, and (4) the end of the book. The benefits of the research were helping students and teachers deepen the material for writing persuasive texts.